2017
DOI: 10.3390/ijms18061268
|View full text |Cite
|
Sign up to set email alerts
|

An Isoform of Nedd4-2 Plays a Pivotal Role in Electrophysiological Cardiac Abnormalities

Abstract: We have previously shown that neural precursor cell-expressed developmentally downregulated gene 4-2 (Nedd4-2) isoforms with a C2 domain are closely related to ubiquitination of epithelial sodium channel (ENaC), resulting in salt-sensitive hypertension by Nedd4-2 C2 targeting in mice. The sodium voltage-gated channel alpha subunit 5 (SCN5A) gene encodes the α subunit of the human cardiac voltage-gated sodium channel (I Na), and the potassium voltage-gated channel subfamily H member 2 (KCNH2) gene encodes rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recent findings in HEK293 cells and neonatal rat cardiomyocytes indicate that increased calcium levels (as observed during heart failure) enhance Nedd4-2 expression and consequent ubiquitylation and downregulation of Na v 1.5 [23]. Furthermore, mice deficient for the Nedd4-2 C2 isoform (isoform containing a C2 domain in the N-terminus) displayed electrocardiographic signs of cardiac conduction and repolarization abnormalities in the absence of overt cardiac structural abnormalities [24]. However, no molecular or functional measurements of ion channel expression/function were performed, and it is unclear to what extent the observed alterations are primary or secondary to the renal phenotype present in these mice [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings in HEK293 cells and neonatal rat cardiomyocytes indicate that increased calcium levels (as observed during heart failure) enhance Nedd4-2 expression and consequent ubiquitylation and downregulation of Na v 1.5 [23]. Furthermore, mice deficient for the Nedd4-2 C2 isoform (isoform containing a C2 domain in the N-terminus) displayed electrocardiographic signs of cardiac conduction and repolarization abnormalities in the absence of overt cardiac structural abnormalities [24]. However, no molecular or functional measurements of ion channel expression/function were performed, and it is unclear to what extent the observed alterations are primary or secondary to the renal phenotype present in these mice [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice deficient for the Nedd4-2 C2 isoform (isoform containing a C2 domain in the N-terminus) displayed electrocardiographic signs of cardiac conduction and repolarization abnormalities in the absence of overt cardiac structural abnormalities [24]. However, no molecular or functional measurements of ion channel expression/function were performed, and it is unclear to what extent the observed alterations are primary or secondary to the renal phenotype present in these mice [24]. Our current study is the first to directly investigate the functional in vivo role of the PY-motif in the cardiomyocyte environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to determine detailed characteristics of salt-sensitive hypertension of the mice, we tried a mineral corticoid receptor antagonist treatment for Nedd4-2 C2 KO mice. Finally, us and other authors [63,64], have previously found that Nedd4-2 C2 KO mice showed eplerenone-resistant salt-sensitive hypertension [65] and enhanced electrophysiological abnormalities, after myocardial infarction [66], suggesting a pivotal role of the Nedd4-2 isoform with C2 domain for cardio-renal association, with regards to target-organ damages of the subjects with salt-sensitive hypertension.…”
Section: Generation Of Nedd4-2 C2 Ko Mice and Discovery Of Salt-sensitive Hypertension With Potential Contributions To Cardio-renal Involmentioning
confidence: 69%
“…Ultimately, we found that the lack of single isoform of the gene caused a significant change in vivo, resulting in a higher oral salt intake suppressing sodium excretion in urine and elevated blood pressures, the pathophysiology of which is called "salt-sensitive" [62]. In accordance with human genetic studies, the impairment of tubular sodium transport might be pivotal in the onset and development of salt-sensitive hypertension [65,66].…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, calcium-mediated increase in NEDD4-2 induced Nav1.5 ubiquitylation with a resultant reduction in Nav1.5 cardiomyocyte membrane density in HF [ 186 ]. Mutations in the gene encoding Nav1.5, SCN5A, have been associated with various arrhythmic disorders such as long QT syndrome, Brugada syndrome, and sick sinus syndrome, indicating the association of NEDD4-2 with cardiac arrhythmia [ 209 , 210 ].…”
Section: Other Cardiac Disease and Hect-type E3 Ligasementioning
confidence: 99%